Lack of antimicrobial activities of Dicranopteris linearis extracts and fractions - Zakaria, Zainul Amiruddin; Mat Desa, A.; Ramasamy, Kalavathy; Ahmat, Norizan; Tengku Mohamad, Tengku Azam Shah; Israf Ali, Daud Ahmad; Sulaiman, Mohd Roslan (Academic Journals, 2010)
The aim of the present study is to determine the antimicrobial activity of the aqueous, chloroform and methanol extracts of the leaves of Dicranopteris linearis (Gleicheniaceae) using the micro-broth dilution method. The leaves of D. linearis were soaked separately in distilled water (dH2O), chloroform and methanol in the ratio of 1:20 (w/v) for 72 h at room temperature, while some part of the methanol extracts was also partitioned with hexane, chloroform and methanol. The target microbe used were Staphylococcus aureus 25923, S. aureus 33591 (a methicillin-resistant S. aureus (MRSA) isolate), S. aureus 700699 (a vancomycin-intermediate resistant S. aureus (VISA) isolate), S. aureus 156 (a vancomycin-resistant S. aureus (VRSA) isolate), Escherichia coli 35218 and Candida albicans 10231. The results obtained show that the methanol extract was the most active in antimicrobial testing with the MIC/MBC values of 625 μg/ml. Based on this result, fractionation was carried out on the methanol extract and yielded eleven fractions. Of these, only B5, B6 and B11 fractions were found to be effective against S. aureus 33591 and S. aureus 25927 with MIC/MBC values ranging between 1250 - 2500 μg/ml. In conclusion, the D. linearis possess mild antibacterial activity against the selected panel of microbes, which explained the lack of claimed on the plant antimicrobial activity.